The Practicality of English Material Integrated with Islamic Values for the Eighth-Grade Students of MTSN - Mardianah, Hj.; Tsuraya, Annisa Shofa; Gunawan, Totok; Sakinah, Zaida Haiyun; Ashari, Windi (ETERNAL (English, Teaching, Learning, and Research Journal), 2023)
This research intends to continue previous research that skipped the implementation stage of ADDIE model in developing teaching modules that are integrated with Islamic values, especially for English material. The implementation phase in this research aims to determine the practicality of the module that has been developed. This research used explanatory mixed method design, where the quantitative data are collected first and are more heavily weighted by the qualitative data. The sample of this research is the eighth-grade students (class 8B, 8C, 8D) at MTs Madani Pao-Pao with total are 89 students. The score results of the practicality checklist shows that the module is categorized as practical, which means the module can improve student’s understanding of the material that has been taught, and the module can be used as a source in the learning process. Therefore, it implies that the module can be used as a learning media in learning process and can be useful for teachers, students, and other people who study English, especially for greeting card, recount text, and describing person and thing material.